FACTORS INFLUENCING THE INTERNATIONALIZATION PROCESS OF BRAZILIAN BORN GLOBAL COMPANIES - Souza, Izabel Regina de; Gianezini, Miguelangelo (International Journal of Research -GRANTHAALAYAH, 2020)
This study aimed to identify factors that influence the internationalization of Brazilian born global companies (BGs). The studies on the theme of internationalization have been developed in a specific area and have continuously refined themselves as a theoretical field of high relevance and prominence. These researches seek to follow the speed and changes of international business, especially the studies that focus on the phenomenon of accelerated internationalization or as called, Born Global. A search was carried out – in the annals of events (EnAnpad and Semead), Brazilian international business journals, and at Google ScholarTM – to identify empirical studies on the theme "internationalization of Brazilian born global companies." The results found point to a diversity of factors that can influence BG companies' internationalization process, such as networks, geographic location, product differentiation, intensive use of technologies, and product innovation. However, the most relevant issue (and that demands new specific studies) is the "profile of the entrepreneur" as a factor of significant influence in the internationalization of the Brazilian BGs.